Executive equity incentives and opportunistic manager behavior: new evidence from a quasi-natural experiment - Martin Nienhaus (Review of Accounting Studies, 2021)
This study provides plausible causal evidence on the effect of executive equity incentives on opportunistic manager behavior. I exploit a unique setting created by the introduction of Financial Accounting Standard (FAS) 123R in 2005, which led to an exogenous increase in the cost of option pay, causing a substantial decline in option pay for some firms while leaving others largely unaffected. Using difference-in-differences analyses with a treatment group of firms that show a decline in option pay and two control groups, I find that the likelihood of a treatment firm meeting or beating analyst forecasts decreases by 14–20%. The results show that the relatively high levels of meet-or-beat before FAS 123R were largely driven by real activities manipulation such as abnormal asset sales and sales manipulation to beat analysts' benchmarks, while accrual manipulation and analyst management were less relevant. Together, the results suggest that equity incentives encourage opportunistic actions to meet or beat earnings expectations, and a decline in option pay results in a decline in earnings management to meet earnings expectations.
Keywords: M41; G38; 650; Executive compensation; Equity incentives; Beating analysts' forecasts; FAS 123R; Quasi-natural experiment